Pernikahan Di Bawah Umur Dalam Perspektif Hukum Perkawinan - Fadhlullah Fadhlullah; Novi Andriani (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Underage marriages are marriages that are not in accordance with Law Number 1 of 1974 on Marriage. Article 7 paragraph (1) states "that marriage is onlypermitted if the male has reached the age of 19 and the woman has reached the age of 16". Underage marriages in Gunung Meriah Subdistrict, Aceh Singkil District are caused by several factors including low levels of education, a narrow mindset in understanding and understanding the nature and purpose of marriage, fear of parents that their children will become spinsters, and the result of free promiscuity they traveled, so the occurrence of pregnancy out of wedlock. Impact on underage marriages is affecting psychological conditions, social conditions in society, divorce, and impacting the law